2015
DOI: 10.4149/neo_2015_111
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil factor 3 is required for differentiation of thyroid follicular cells and acts as a context-dependent tumor suppressor

Abstract: Trefoil factor 3 (TFF3) is overexpressed in a variety of solid epithelial cancers, where it has been shown to promote migration, invasion, proliferation, survival and angiogenesis. On the contrary, in the majority of thyroid tumors, it is downregulated, yet its role in the development of thyroid cancer remains unknown. Here we show that TFF3 exhibits strong cytoplasmic staining of normal thyroid follicular cells and colloid and the staining is increased in hyperfunctioning thyroid nodules, while it is decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…[ 5 ]). By contrast, a recent study demonstrated that TFF3 is downregulated in most thyroid tumors [ 31 ]. Along this line our study revealed, that compared to the healthy human retina TFF3 mRNA (data not shown) and TFF3 protein expression levels are likewise below detection levels in primary retinoblastoma samples ( S2 Fig ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[ 5 ]). By contrast, a recent study demonstrated that TFF3 is downregulated in most thyroid tumors [ 31 ]. Along this line our study revealed, that compared to the healthy human retina TFF3 mRNA (data not shown) and TFF3 protein expression levels are likewise below detection levels in primary retinoblastoma samples ( S2 Fig ).…”
Section: Discussionmentioning
confidence: 98%
“…In human corneal epithelia cells, proliferation likewise decreased 24 h after stimulation with recombinant TFF3 [ 42 ]. Along this line, forced expression of TFF3 significantly reduced proliferation of anaplastic thyroid cancer cells [ 31 ]. By contrast, Sun et al (2014) demonstrated that TFF3 promotes proliferation of gastric mucosal epithelial cells [ 43 ] and most recent studies likewise reported that rTFF3 enhanced the proliferation of gastric endothelial and human corneal epithelial cells [ 44 ; 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to cancer, TFF3 has been proposed to function both as an oncogene and as a tumor suppressor. Thus, high TFF3 expression has been associated with favorable prognosis in ovarian cancer [ 22 ] and with low grade in early stage breast cancer [ 23 ], and TFF3 seems to act as a tumor suppressor in thyroid cancer [ 24 ]. In contrast, TFF3 protein overexpression has been linked with aggressive disease in colon, gastric, and mammary cancer [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently TFF3 has been described as a gene that could function as an oncogene or oncosuppressor in dependence on the cellular context. In fact, in many types of solid tumors an increase of TFF3 expression level was observed, while in all thyroid cancers of follicular cell origin its expression was decreased when in normal thyroid it was highly expressed [31]. Other known overexpressed genes on chr21 are CSTB (cystatin B) and SOD1 (superoxide dismutase 1, soluble) (Table 2) encoding, respectively, for a protease inhibitor that has been reported to protect neurons from oxidative stress and for a free superoxide radical destroyer that controls the redox state of the cells.…”
Section: Discussionmentioning
confidence: 99%